Herpesvirus and subsequent Usutu virus infection in a great grey owl (Strix nebulosa) at the Ljubljana Zoo, Slovenia - Žlabravec, Zoran; Kvapil, Pavel; Slavec, Brigita; Zorman-Rojs, Olga; Švara, Tanja (Animals, 2024)
Herpesvirus (HV) has been known to cause disease in owls, with various clinical signs and outcomes for the last several decades. The HV DNA polymerase gene was detected in oropharyngeal and cloacal swabs of a male great grey owl (Strix nebulosa) in a zoological collection in Ljubljana, Slovenia. In the following 4 months, despite continuous HV detection in swabs, no clinical signs with a clear link to HV disease were observed. Hepatoprotective and immunostimulant therapies applied during this period did not prevent HV shedding. Therefore, peroral antiviral therapy with acyclovir (150 mg/kg q24 h for seven days) was performed, and the owl tested negative at the next sampling and remained negative for the next 8 months. After that, the owl again tested positive for HV presence, and the same protocol with antiviral therapy was performed. After 3 weeks with a negative test for HV presence, without any clinical signs of illness, the owl suddenly died because of Usutu virus (USUV) infection. Among all the owls at the zoo, interestingly, only the HV-positive great grey owl died because of USUV infection. The USUV sequence detected and obtained in this study clusters together with other Europe 2 sequences detected in neighboring countries. Our study shows the potential of acyclovir therapy in the prevention of herpesvirus shedding and, moreover, lowering the possibility for spreading HV to other owls and birds. To the best of our knowledge, this is the first report of HV presence and USUV infection in a great grey owl in Slovenia.